KONTRIBUSI PENYULUH AGAMA ISLAM SEBAGAI PENDIDIK NONFORMAL DALAM MENAMBAH WAWASAN KEBERAGAMAAN PADA MASYARAKAT KEC. TANETE RIATTANG BARAT KAB. BONE - Sri Anugrah Indriani (UIN Sunan Kalijaga Yogyakarta, 2019)
AbstractIslamic religious education is not only obtained at the level of formal education. Education in the community environment also contributes to the development of religious diversity in society. The presence of Islamic religious instructors as non-formal educators is the answer to the needs of educators for the community. People who come from various backgrounds have their own place to study Islamic education. This research uses field studies that directly involve the community, conduct interview techniques, collect data and direct observation in the field. The results of this study explain that the insights of religious diversity so far have been good. The use of various methods greatly influences the insights received by the community. Therefore, Islamic extension workers as non-formal educators also need to prepare themselves to face the challenges that exist in the community environment. Keywords: islamic religious instructor, insight into the diversity of society.